2008
DOI: 10.1016/j.eurpsy.2008.01.1420
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological functioning in adolescents with first episode psychosis: A two-year follow-up study

Abstract: Cognitive deficits are a core feature of psychotic disorders. Both in adult and adolescent populations, studies have shown that patients with psychosis have poorer cognitive functioning than controls. The cognitive domains that seem to be affected are mainly attention, working memory, learning and memory, and executive function. However, with regard to the trajectory of cognitive function throughout the illness, there is still a dearth of prospective data in patients who develop psychosis during adolescence. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 48 publications
2
23
0
1
Order By: Relevance
“…We interpret these results as suggesting a large degree of independence between psychopathology and cognitive deficits in EOS both at illness onset and chronic phase. This is consistent with most previous studies [7;11;24;46;81], although not all [53].…”
Section: Discussionsupporting
confidence: 94%
“…We interpret these results as suggesting a large degree of independence between psychopathology and cognitive deficits in EOS both at illness onset and chronic phase. This is consistent with most previous studies [7;11;24;46;81], although not all [53].…”
Section: Discussionsupporting
confidence: 94%
“…This study found that earlier onset corresponds linearly with the severity of the course of the disorder and appears to have some prognostic impact [71]. Young age at onset might have a detrimental effect on outcome because of impact at very crucial times of development and neurobiological maturation in childhood and adolescence, which prove to have more lasting effects in terms of both cognitive and psychosocial impairments [1,32,35,72]. …”
Section: Discussionmentioning
confidence: 99%
“…A recently published controlled longitudinal study found a significant increase in a composite measure of global cognitive function over a 2-year follow-up period in a mixed group of patients with EOS or other psychosis and the control group [37]. Regarding development of intelligence, premorbid intellectual performance deficits aggravate around the time of onset of very early onset schizophrenia also referred to as childhood onset schizophrenia (COS; onset by age 12), and a mean loss of 9.96 FSIQ points has been observed in the period from 2 years before illness onset to 1.7 years after [16].…”
Section: Introductionmentioning
confidence: 98%